2012
DOI: 10.1128/aac.05158-11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Thermal Energy on Bactericidal Action of Photolysis of H 2 O 2 in Relation to Acceleration of Hydroxyl Radical Generation

Abstract: The purpose of the present study is to evaluate the effect of thermal energy on the yield of and the bactericidal action of hydroxyl radical generated by photolysis of H 2 O 2 . Different concentrations of H 2 O 2 (250, 500, 750, and 1,000 mM) were irradiated with light-emitting diodes (LEDs) at a wavelength of 400 ؎ 20 nm at 25°C to generate hydroxyl radical. The 500 mM H 2 O 2 was irradiated with the LEDs at different temperatures (25, 35, 45, and 55°C). Electron spin resonance spin trapping analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
(23 reference statements)
0
33
0
Order By: Relevance
“…This finding suggests that photolysis of H 2 O 2 can effectively kill not only bacteria but also fungi. Shirato et al evaluated the effect of thermal energy on the yield of and the bactericidal action of hydroxyl radicals generated by photolysis of H 2 O 2 [53]. The results demonstrated that thermal energy accelerated the generation of hydroxyl radicals by photolysis of H 2 O 2 , which in turn resulted in a synergistic bactericidal effect of hydroxyl radicals and thermal energy.…”
Section: Application Of Hydroxyl Radicals To Disinfection Treatmentmentioning
confidence: 99%
“…This finding suggests that photolysis of H 2 O 2 can effectively kill not only bacteria but also fungi. Shirato et al evaluated the effect of thermal energy on the yield of and the bactericidal action of hydroxyl radicals generated by photolysis of H 2 O 2 [53]. The results demonstrated that thermal energy accelerated the generation of hydroxyl radicals by photolysis of H 2 O 2 , which in turn resulted in a synergistic bactericidal effect of hydroxyl radicals and thermal energy.…”
Section: Application Of Hydroxyl Radicals To Disinfection Treatmentmentioning
confidence: 99%
“…As a result, the amount of released ions was evaluated by weighing the specimens before and after immersion test using an electronic analytical balance (GH-200, A&D, Tokyo, Japan). Amount of released ions was calculated as µg/cm 2 14) . DMPO was the spin trapping agent.…”
Section: Experimental Led Devicementioning
confidence: 99%
“…In our previous studies 1,2) , we have developed a novel disinfection technique, based on hydroxyl radicals generated by photolysis of H 2O2, which could effectively kill bacteria in biofilms within 3 min. Therefore, this new disinfection technique can be used as an adjunctive treatment for caries, periodontitis, and root canal infection by delivering light together with H 2O2 to the lesion site.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that proper denture cleaning should include chemical disinfection [5][6][7] . In our laboratory, we developed a new chemical disinfection method based on the photolysis of hydrogen peroxide (H 2O2) 8,9) . When removable dentures were immersed in H2O2 irradiated with lightemitting diode (LED) light at a wavelength of 405 nm, microorganisms in denture plaque were rapidly and effectively killed by hydroxyl radicals generated from the photolysis of H 2O2 10) .…”
Section: Introductionmentioning
confidence: 99%